Ca II triplet spectroscopy of small magellanic cloud red giants. II. abundances for a sample of field stars - Parisi, Maria Celeste (2015)
We have obtained metallicities of ∼360 red giant stars distributed in 15 Small Magellanic Cloud (SMC) fields from near-infrared spectra covering the Ca II triplet lines using the VLT + FORS2. The errors of the derived [Fe/H] values range from 0.09 to 0.35 dex per star, with a mean of 0.17 dex. The metallicity distribution (MD) of the whole sample shows a mean value of [Fe/H] = -1.00 ± 0.02, with a dispersion of 0.32 0.01, in agreement with global mean [Fe/H] values found in previous studies. We find no evidence of a metallicity gradient in the SMC. In fact, on analyzing the MD of each field, we derived mean values of [Fe/H] = -0.99 ± 0.08 and [Fe/H] = -1.02 ± 0.07 for fields located closer and farther than 4° from the center of the galaxy, respectively. In addition, there is a clear tendency for the field stars to be more metal-poor than the corresponding cluster they surround, independent of their positions in the galaxy and of the clusters' age. We argue that this most likely stems from the field stars being somewhat older and therefore somewhat more metal-poor than most of our clusters. © 2010. The American Astronomical Society.